Police Communication Strategy in Combating Hoaxes - Tarmiji, Muhamad (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
This article examines the communication strategy of the Central Jakarta Metro Police (Polres Jakpus) in campaigning anti-hoax to make Central Jakarta clean from hoaxes and create a sense of security in the community. This research was conducted in Jakarta for three months, from June to August 2018. Using a qualitative case study approach, primary data is collected by conducting interviews and observations, and secondary data is collected through document searches from books, journals, and other internet media sources. The results showed that the communication strategy carried out by the Polres Jakpus in an anti-hoax campaign put forward the preventive action conducted by the Sat Binmas through Bhabinkamtibmas. This was marked by appeals and socialization by Bhabinkamtibmas through posters, leaflets, banners, and door-to-door appeals from people's homes. Polres Jakpus Public Relations also carried out the campaign activity through exciting content on social media, campaigning not readily to trust and spreading the news that is not necessarily true. The activity also included socializing about criminal law for a hoax spreader. To cite this article (7th APA style): Tarmiji, M. (2023). Police communication strategy in combating hoaxes. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(1), 42-59.